Interaction Between the Protection of the Rights of Indigenous Peoples and Foreign Investment: Regulation in Indonesia - Kinanti, Fatma Muthia; Wiko, Garuda; Nurbani, Erlies Septiana (Padjadjaran Journal of International Law, 2023)
Abstract Indigenous peoples in Indonesia are still marginalized since most of them are still poor and oppressed due to inequality in their sources of life. On the other hand, it is not uncommon for foreign investment activities to harm the surrounding environment including indigenous peoples. This article discusses the interaction between indigenous people’s rights and foreign investment regulations in Indonesia and what the Government of Indonesia must do to balance the need to improve the national economy and protect indigenous peoples. To answer these, the articles explained and mapped the international and national regulations relating to indigenous people and foreign investment. The data then analyzed to show how the Indonesian Government may improve the protection of indigenous peoples' rights in relation to foreign investment activities in Indonesia. It is found that Indonesia has already ratify International Convention that provide the protection of Indigenous people including relating to foreign investment (economic) activities. To ensure its implementation several steps must be taken i.e.: adopting an international investment agreement (IIA), bilateral investment treaty (BIT) and investment contract that provide assurance for the protection of indigenous people, ensuring the promulgation of Indigenous Peoples’ Rights Bill and Amend the Investment Law and Establish Implementing Regulations related to the Job Creation Law which enforce the concept of indigenous community protection in relation foreign investment activities. Abstrak Masyarakat adat di Indonesia masih terpinggirkan karena sebagian besar masih miskin dan tertindas akibat ketimpangan sumber penghidupan. Di sisi lain, tidak jarang kegiatan penanaman modal asing merusak lingkungan sekitar termasuk masyarakat adat. Artikel ini membahas interaksi antara hak-hak masyarakat adat dan peraturan penanaman modal asing di Indonesia dan apa yang harus dilakukan Pemerintah Indonesia untuk menyeimbangkan kebutuhan untuk meningkatkan ekonomi nasional dan melindungi masyarakat adat. Untuk menjawabnya, pasal-pasal tersebut menjelaskan dan memetakan peraturan internasional dan nasional yang berkaitan dengan masyarakat adat dan penanaman modal asing. Data tersebut kemudian dianalisis untuk menunjukkan bagaimana Pemerintah Indonesia dapat meningkatkan perlindungan hak-hak masyarakat adat terkait dengan kegiatan investasi asing di Indonesia. Ditemukan bahwa Indonesia telah meratifikasi Konvensi Internasional yang memberikan perlindungan terhadap masyarakat adat termasuk yang berkaitan dengan kegiatan investasi (ekonomi) asing. Untuk memastikan implementasinya beberapa langkah harus diambil yaitu: mengadopsi perjanjian investasi internasional (IIA), perjanjian investasi bilateral (BIT) dan kontrak investasi yang memberikan jaminan perlindungan masyarakat adat, memastikan pengesahan RUU Hak Masyarakat Adat dan Perubahan UU Penanaman Modal dan Menetapkan Peraturan Pelaksana terkait UU Cipta Kerja yang memberlakukan konsep perlindungan masyarakat adat dalam kaitannya dengan kegiatan penanaman modal asing.